2016
DOI: 10.1007/s00432-016-2168-6
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial growth as an aggressive growth pattern in primary lung cancer

Abstract: We firstly reported on IG in various types of primary lung cancer. IG appears to be a sign of an aggressive lung cancer phenotype, mainly found in pleomorphic carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have shown that LIMA may originate from type II alveolar epithelial or Clara cell metaplastic lesions, and further develop atypical hyperplasia and carcinogenesis[ 14 , 15 ]. Tumor cells in IMAs are highly discrete, and show poor adhesion; These easily diffuse widely through alveolar pores and small airways, which is an important reason for their diffuse distribution[ 16 , 17 ]. In a study by Cha et al [ 18 ], 13.9% of IMAs were initially identified as pneumonia, which is much higher than the rate of initial misdiagnosis of invasive non-mucinous adenocarcinomas as pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that LIMA may originate from type II alveolar epithelial or Clara cell metaplastic lesions, and further develop atypical hyperplasia and carcinogenesis[ 14 , 15 ]. Tumor cells in IMAs are highly discrete, and show poor adhesion; These easily diffuse widely through alveolar pores and small airways, which is an important reason for their diffuse distribution[ 16 , 17 ]. In a study by Cha et al [ 18 ], 13.9% of IMAs were initially identified as pneumonia, which is much higher than the rate of initial misdiagnosis of invasive non-mucinous adenocarcinomas as pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…The pulmonary interstitium, pleura and blood vessels of the lung are generally unaffected. Tumor cells in IMAs are highly discrete, poor adhesion, easily spread widely through alveolar pores and small airways, which is an important reason for its diffuse distribution [ 9 , 10 ]. Middle-aged and elderly people are susceptible to this disease, and the incidence rate is higher in women than in men.…”
Section: Discussionmentioning
confidence: 99%
“…The specific histological pattern was originally described in lung metastatic pattern from sarcoma and was correlated with aggressiveness such as vascular and lymphatic invasion followed by poor prognosis. 4 Later, Suzuki et al 5 also reported the interstitial growth pattern rarely seen in primary lung carcinoma specimens, especially in pleomorphic carcinoma and correlated with its aggressiveness. Pathologically, the 'interstitial growth pattern' was considered to be present if all of the following three findings were found in at least one area: (i) tumor cells continuously spreading from the peripheral area of the tumor; (ii) clusters of tumor cells infiltrating in the alveolar septum without © 2020 Japanese Society of Pathology and John Wiley & Sons Australia, Ltd pneumocyte destruction; and (iii) overlying type II pneumocytes showing hyperplastic change.…”
Section: Letter To the Editormentioning
confidence: 98%